2018
DOI: 10.1177/0271678x18790139
|View full text |Cite
|
Sign up to set email alerts
|

Safety, feasibility, and potential efficacy of intraarterial selective cooling infusion for stroke patients treated with mechanical thrombectomy

Abstract: This is a prospective non-randomized cohort study of 113 consecutive patients to investigate the safety and efficacy of a short-duration intraarterial selective cooling infusion (IA-SCI) targeted into an ischemic territory combined with mechanical thrombectomy (MT) in patients with large vessel occlusion-induced acute ischemic stroke (AIS); 45/113 patients underwent IA-SCI with 350 ml 0.9% saline at 4℃ for 15 min at the discretion of the interventionalist. Key parameters such as vital signs and key laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(142 citation statements)
references
References 32 publications
1
125
0
Order By: Relevance
“…The systemic temperature was measured and only mildly reduced (maximum 0.3°C). In a non-randomized cohort study (113 patients) using the same cooling protocol, the authors report a small but significant reduction in infarct volume and trend towards clinical benefit warranting an initiation of a larger randomized controlled trial 21…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The systemic temperature was measured and only mildly reduced (maximum 0.3°C). In a non-randomized cohort study (113 patients) using the same cooling protocol, the authors report a small but significant reduction in infarct volume and trend towards clinical benefit warranting an initiation of a larger randomized controlled trial 21…”
Section: Discussionmentioning
confidence: 98%
“…To address these issues, localized delivery of cold fluids through standard catheters has been explored 19 20. Recently published clinical work is encouraging, showing the potential for infarct reduction, motivating a larger randomized controlled trial to further evaluate efficacy 21…”
Section: Introductionmentioning
confidence: 99%
“…Finally, intra-arterial selective cooling, a promising nonpharmacological treatment, can easily be performed shortly after thrombectomy to induce partial hypothermia in the ischemic area. [86][87][88][89] In previous pilot study, intra-arterial selective cooling has been performed in AIS undergoing EVT. [90] Cold 0.9% sodium chloride (4°C) was infused to the ischemic territory before recanalization (10 ml/min for 5 min) through microcatheter and postrevascularization (30 ml/min for 10 min) through the guiding catheter.…”
Section: Following Revascularizationmentioning
confidence: 99%
“…Recent clinical trials have demonstrated the safety and efficacy of TH in stroke patients. [16] Taken together, this evidence suggests that TH may be the neuroprotective agent that stroke patients Figure 1: Theoretical interplay between therapeutic hypothermia and acute ischemic stroke. This figure summarizes the primary pathways by which acute ischemic stroke damages the brain parenchyma, resulting in functional deficits for stroke patients.…”
Section: Therapeutic Hypothermiamentioning
confidence: 95%
“…In 2017, a prospective, nonrandomized control study (n = 113) investigated the feasibility of selective TH in AIS patients when combined with mechanical thrombectomy (n = 45) versus a control group that underwent standard treatment (n = 68). [16] In the cooling cohort, ischemic regions were infused with 50 ml of cold saline (4°C) at 10 ml/min before recanalization, utilizing a microcatheter that was put across the thrombus. After recanalization with mechanical thrombectomy, 4°C saline was infused at 30 ml/min for 10 min.…”
Section: Current State Of Systemic Therapeutic Hypothermiamentioning
confidence: 99%